(untitled) (Revista ABRA, 2014)
Vulnerability of small island spaces comes fromtheir lack of resources of every kind, including humanones, which sometimes turns them into passive subjectsof natural hazards and other negative contingencies,particularly those of economic and social nature. In thisregard, the shortage of space directly affects the progressand welfare of these territories, which must address thedifficult task of finding a model of sustainable developmentthat ensures an autonomous economic growth over thelong term without compromising the environment. Thispaper will discuss the need for a comprehensive planningand management of the island territories as a means toachieve these ends and, above all, as the main tool forreducing the